Development of the Unified Theory of Acceptance and Use of Technology Model in the Acceptance of Electronic Medical Records Systems at Colonel Abundjani Bangko Hospital - S, Jenti Yulita; Ginting, Christmis Novalinda; Nasution, Sri Wahyuni (Journal La Medihealtico, 2023)
This type of research is quantitative with an analytical observational approach with a cross sectional design. This research was conducted at the Colonel Abundjani Bangko Hospital from September to October 2023. The population in this study were all health workers associated with the implementation of medical records consisting of doctors, nurses, medical records officers and pharmacists at the Colonel Abundjani Bangko Hospital. 152 people (Total population). Data analysis was carried out univariate, bivariate (Chi Square), and multivariate (logistic regression). The results of the research show that there is an influence of the perception aspect of usability on the acceptance of the Electronic Medical Record system (p< 0,05). There is an influence of job suitability aspects on the acceptance of the Electronic Medical Record system (p< 0,05). There is an influence of the relative profit aspect on the acceptance of the Electronic Medical Record system (p< 0,05). There is an influence of social influence aspects on the acceptance of the Electronic Medical Record system (p< 0,05). There is an influence of the facility aspect on the acceptance of the Electronic Medical Record system (p< 0,05). The dominant variable influencing the acceptance of the Electronic Medical Record system at Colonel Abundjani Bangko Hospital is the social aspect variable. The conclusion in this research is that there is an influence of the development of the Unified Theory of Acceptance and Use of Technology (UTAUT) Model in the acceptance of the Electronic Medical Record system at the Colonel Abundjani Bangko Hospital.